Controlled Subsurface Drainage as a Strategy for Improved Water Management in Irrigated Agriculture of Uzbekistan†. (26th July 2018) - Dukhovny, Victor; Kenjabaev, Shavkat; Yakubov, Shavkat; Umirzakov, Gulomjon
Abstract: An existing conventional drainage (CVD) was modified to control the flow from the drainage lateral and to control the groundwater table depth on a portion of irrigated winter wheat during the 2014–2015 cropping season in the Fergana Valley, Uzbekistan. Drainage outflow at one of two drainages was controlled (CTD), while the other was free (CVD). The cumulative drainage water volume from the CVD treatment was 22% greater than the CTD treatment. The flow‐weighted mean salt concentration of the drainage water was on 7% lower in the CTD treatment (2.08 mS cm −1 ) compared to the CVD treatment (2.24 mS cm −1 ). The ratio of soil water content in the 1 m soil profile between inspection sumps A and B (1) versus B and the open collector (2) was 1.2, suggesting that the upper part of the field contained 20% more soil moisture. Conversely, the ratio of the groundwater table depth between (1) and (2) was 0.78, indicating that the groundwater table of the upper portion of the field was 47 cm (22%) shallower than the lower part. Thus, CTD increased the moisture storage of the soil layer in the upper part of the field. Managing the groundwater table resulted in less water stress between irrigation events and increased grain yields. © 2018 John Wiley & Sons, Ltd.